Dominant Factor Causing Work Accidents Based On The Loss Causation Model At Pt. Barata Indonesia - Vita Dwi Rohmah Nur Rosanti; Inayah, Zufra (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Production activities in each industrial environment have risks of occupational hazards. Reports of work accident cases in Indonesia in the manufacturing industry sector over the last two years have increased from 114,000 cases in 2019 to 177,000 cases in 2020. Work accident investigation at PT. Barata Indonesia in 2022-2023 of the 626 workers, there were 6% of work accident cases. The loss causation model theory is a development of work accident theory at management factors to human factors or workers who are directly involved with materials. The research aims to analyze the dominant factors that most influence work accidents at PT. Barata Indonesia. Type of quantitative research with analytical observational research methods (crosssectional). The research sample was 308 workers at PT Barata Indonesia. The data analysis used was chi-square and logistic regression. The result of this study is that the dominant factor that has the most influence on work accidents at PT Barata Indonesia is the immediate cause factor, namely compliance with work instructions with a significance of 0.002 < 0,05, and a coefficient value of 2,124, and a CI: 1,304-3,460, meaning that there is a influence between compliance with work instructions on work accidents and a chance of getting a work accident 2 times higher when not complying with work instructions. Therefore, some preventive efforts are needed to prevent work accidents, especially in the manufacturing industry